Museums and social change : challenging the unhelpful museum - Chynoweth, Adele; Lynch, Bernadette; Petersen, Klaus, 1965-; Smed, Sarah (New York : Routledge, 2020)
"Museums and Social Change explores the ways museums can work in collaboration with marginalised groups to work for social change and, in so doing, re-think the museum. Drawing on the first-hand experiences of museum practitioners and their partners around the world, the volume demonstrates the impact of a shared commitment to collaborative, reflective practice. Including analytical discussion from practitioners in their collegial work with women, the homeless, survivors of institutionalised child abuse and people with disabilities, the book draws attention to the significant contributions of small, specialist museums in bringing about social change. It is here, the book argues, that the new museum emerges: when museum practitioners see themselves as partners, working with others to lead social change, this is where museums can play a distinct and important role. Emerging in response to ongoing calls for museums to be more inclusive and participate in meaningful engagement, Museums and Social Change will be essential reading for academics and students working in museum and gallery studies, librarianship, archives, heritage studies and arts management. It will also be of great interest to those working in history and cultural studies, as well as museum practitioners and social activists around the world"--
OCLC-licensed vendor bibliographic record.
Keywords: Museums and community; Museums -- Social aspects; Museums -- Management; People with social disabilities -- Education; POLITICAL SCIENCE / General